DEVELOPMENT OF ORGANIZING EVENTS AND MEETINGS INCENTIVES CONFERENCES EXHIBITIONS BASED ON PROJECT BASED LEARNING TO IMPROVE CAREER MATURITY OF VOCATIONAL HIGH SCHOOL STUDENTS IN BULELENG REGENCY - Parma, I Putu Gede; Mahardika, A.A. Ngurah Yudha Martin; Andiani, Nyoman Dini (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study explores the development of a learning model for organizing Events and Meetings, Incentives, Conferences, and Exhibitions (MICE) based on Project-Based Learning (PjBL) to enhance the career maturity of vocational high school students in Buleleng Regency. The tourism and creative industries demand graduates who are not only technically competent but also possess strong soft skills, leadership abilities, and career readiness. However, many vocational students face challenges in linking theoretical knowledge with real-world applications, particularly in dynamic fields such as MICE. This approach encourages active learning, collaboration, critical thinking, and self-directed exploration. The research employs a Research and Development (R&D) method, involving needs analysis, model design, implementation, and evaluation stages across several vocational schools in Buleleng. Data collection methods include observation, questionnaires, interviews, and documentation. More importantly, it fosters a greater sense of responsibility, self-efficacy, and future career orientation. Teachers reported increased student engagement and initiative, while students expressed higher confidence in their career planning and readiness for the MICE industry. This study concludes that a PjBL-based MICE curriculum is a strategic innovation for vocational education, aligning with the demands of the 21st-century workforce. It is recommended that similar models be adopted in other regions to bridge the gap between education and industry, thereby supporting the development of skilled, mature, and career-ready graduates.